If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -3x = -6x + 2 Reorder the terms: 11 + -3x = 2 + -6x Solving 11 + -3x = 2 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 11 + -3x + 6x = 2 + -6x + 6x Combine like terms: -3x + 6x = 3x 11 + 3x = 2 + -6x + 6x Combine like terms: -6x + 6x = 0 11 + 3x = 2 + 0 11 + 3x = 2 Add '-11' to each side of the equation. 11 + -11 + 3x = 2 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 2 + -11 3x = 2 + -11 Combine like terms: 2 + -11 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 3z+7=z+10 | | cot(x)=2.4 | | log(8)(k-8)=2 | | x^3-x^2+15*x+17=0 | | V=Bcy | | 4sin(2x)+2=0 | | 0.2x+4.4=3.3 | | (1128*2)+(120*3)=x+(x*0.2) | | -2(a-6)=-36 | | z=0.06-50/6 | | 70(-8/5) | | 2y+3=33 | | x^2-4x+4+x^2-18x+81=x^2 | | 6(c+2)-x=4(x+4)+7 | | 6-6n+3n=42-84 | | ab-9a+b-45= | | -20/-4= | | 6-6n+3n=42-8 | | 5-97-09= | | 7x^2+27x+18=0 | | 4(n+6)+4n=8+8(2n+6) | | 2e^5x=6e^4x | | -3(4s-4)-12=-2(9s+1)-2 | | 52=9x+2 | | 49=6x+1 | | 16=10b | | 8x+15=12x+3 | | 5y+6=2y+9 | | 39+6x+6=x^2+2x | | z=X-51/8 | | -11(-9)= | | 3a+2[2+39a-1]=2(3a+4) |